Strategies for Women at Work. - LaRouche, Janice and Regina Ryan. (New York US ARMY LIBRARY, 1984)
This book is dedicated to the countless women who never had the chance to be what they could be, and to all those who have fought to give women that chance.
Keywords: Politics